EFEKTIVITAS PELAKSANAAN PIDANA DENDA DALAM TINDAK PIDANA KORUPSI DI INDONESIA - Windi Ardiansyah; Mohamad Ismed; Hedwig Adianto Mau (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study addresses two legal issues: first, the effectiveness of fines in corruption cases, and second, how fines are implemented as a deterrent for corruption perpetrators. This study aims to determine the extent to which fines are implemented in court decisions and to test their effectiveness in eradicating corruption in Indonesia. In the corruption cases of Muhammad Lutfi, Taufik Ramadhi, and Cokro Nogoro, it was found that judges imposed fines, but their implementation still faces obstacles, particularly when the convict is unable to pay the fine. This situation results in the effectiveness of fines as a legal instrument being less than optimal, often resulting in a lack of maximum deterrent effect. Therefore, strengthening regulations and consistency in the application of fines are needed so that they truly function as a means of law enforcement and eradicating corruption